2011
DOI: 10.1007/s10815-011-9603-z
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Klinefelter men and their relatives towards TESE-ICSI

Abstract: PurposeAt the start of the implementation of TESE-ICSI for Klinefelter men in the Netherlands, we aimed to evaluate their wish to father children and their attitudes towards this artificial reproduction technique.MethodsQuestionnaires were distributed to members of the Dutch Klinefelter Association (n = 365) and to Klinefelter cases known at our Department (n = 58). Questions addressed several aspects: socio-demographic characteristics, ascertainment of diagnosis, children and child wish, and TESE-ICSI. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In a questionnaire-based survey of patients with KS, 90% of respondents expressed a desire to father children (64). However, 70% of them also identified safety concerns with the use of TESE-ICSI, in terms of chromosomal, congenital, or developmental abnormalities in their offspring (64).…”
Section: Genetics Risks To Offspringmentioning
confidence: 99%
See 1 more Smart Citation
“…In a questionnaire-based survey of patients with KS, 90% of respondents expressed a desire to father children (64). However, 70% of them also identified safety concerns with the use of TESE-ICSI, in terms of chromosomal, congenital, or developmental abnormalities in their offspring (64).…”
Section: Genetics Risks To Offspringmentioning
confidence: 99%
“…However, 70% of them also identified safety concerns with the use of TESE-ICSI, in terms of chromosomal, congenital, or developmental abnormalities in their offspring (64). The majority of offspring born to men with KS have been healthy, with a normal 46,XX or 46,XY chromosomal complement (18).…”
Section: Genetics Risks To Offspringmentioning
confidence: 99%
“…Even in bad prognosis patients suffering from Klinefelter syndrome [4] or hypogonadotrophic hypogonadism [5] pregnancies can be achieved. Testicular sperm extraction (TESE) specimens require less surgical expertise than epididymal ones and can be provided by all staff urologists, thus allowing for greater flexibility in scheduling IVF procedures.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of Maiburg et al (68) showed that 70% of men with KS and 74% of their partners would opt for TESE-ICSI in order to father a child. Ninety-five percent of the parents estimated this treatment a valuable option for their sons.…”
Section: How Ethical Is It To Bank Given These Doubts?mentioning
confidence: 99%
“…So, assuming that the technical problems will be solved, there is a willingness to use assisted reproduction to realize a child wish. However, the utilization rate of frozen tissue will also be determined by alternatives and need: in approximately 55% of men spermatozoa can be recovered at adult age, only about 50 percent of men with KS had a partner at the age of 40 (68).…”
Section: How Ethical Is It To Bank Given These Doubts?mentioning
confidence: 99%